Lutein derived from Xenostegia tridentata exhibits anticancer activities against A549 lung cancer cells via hyaluronidase inhibition. - Jaruwan Chatwichien; Natthawat Semakul; Saranphong Yimklan; Nutchapong Suwanwong; Prakansi Naksing; Somsak Ruchirawat (PLoS ONE)
Hyaluronidase has been emerging as a potential target for cancer treatment. Herein, the anticancer effects against A549 NSCLC cells and hyaluronidase inhibitory activity of the ethanol extract of Xenostegia tridentata (L.) D.F. Austin & Staples and its subfractions were investigated. In correlation with their hyaluronidase inhibition, the hexane subfraction exhibited the most potent cytotoxicity, and the ethyl acetate subfraction could significantly inhibit the cancer cell migration. The hexane and ethyl acetate fractions were then further isolated to identify the active compounds responsible for the anticancer and hyaluronidase inhibitory activities. Among the 10 isolated compounds, lutein (5), a previously reported anti-lung cancer agent, showed the strongest inhibition on hyaluronidase enzyme activity. Its anticancer activities were validated. Notably, in addition to demonstrating the potential of X. tridentata extract for NSCLC treatment, this study discloses that hyaluronidase is a potential target for the anticancer activities of lutein. The cellular mechanisms underlying the hyaluronidase inhibitory activity of X. tridentata extract need to be further explored to fully understand how this inhibition contributes to its anti-cancer effects.